2009
DOI: 10.3989/gya.130408
|View full text |Cite
|
Sign up to set email alerts
|

Classification of real farm conditions Iberian pigs according to the feeding regime with multivariate models developed by using fatty acids composition or NIR spectral data

Abstract: Multivariate Classification models to classify real farm conditions Iberian pigs, according to the feeding regime were developed by using fatty acids composition or NIR spectral data of liquid fat samples. A total of 121 subcutaneous fat samples were taken from Iberian pigs carcasses belonging to 5 batches reared under different feeding systems. Once the liquid sample was extracted from each subcutaneous fat sample, it was determined the percentage of 11 fatty acids (C14:0, C16:0, C16:1, C17:0, C17:1, C18:0, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…However, as noted by GarridoVaro et al (2004), a major drawback to the procedures involved both in the current field inspection system and in many of the new certification techniques is that they are costly and laborious.…”
Section: Acorn-grass Weight Gain Index For Iberian Pigsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as noted by GarridoVaro et al (2004), a major drawback to the procedures involved both in the current field inspection system and in many of the new certification techniques is that they are costly and laborious.…”
Section: Acorn-grass Weight Gain Index For Iberian Pigsmentioning
confidence: 99%
“…Research has demonstrated that the analysis of melted fat samples, of intact subcutaneous tissue, and even of live animals, coupled with the use of various mathematical algorithms, represents a promising approach both for predicting the proportions of the four major fatty acids (oleic, palmitic, stearic and linoleic) (De Pedro et al, 1992;GarcíaOlmo et al, 2001;González Martín et al, 2002GarridoVaro et al, 2004; tissue samples under laboratory conditions at room temperature (wavelength range 4002500 nm with a spectral interval step of 2 nm). Skin free transverse sections of subcutaneous adipose tissue were analyzed for each sample.…”
Section: Acorn-grass Weight Gain Index For Iberian Pigsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that NIR data performed somewhat better than the mid-IR data [17]. NIRS has been used extensively to analyze oil content and fatty acid profile in oilseeds such as sunflower [18], rapeseed [19], soybean [20], peanut [21], and castor [22], as well as in other commodities such as cereals [23], forages [24], corn [25], and animal products [26]. Conversely, NIRS has not yet been reported for evaluation of most soybean essential nutrients like tocopherols, saponins, FAs, and flavonoids.…”
Section: Introductionmentioning
confidence: 96%
“…NIRS allows fast spectrometric measurement of several traits in a single analysis provided that the corresponding calibration equations are available. NIRS have been extensively used to analyze oil content and fatty acid profile in oilseeds such as sunflower 10, rapeseed 11, soybean 12, peanut 13, and castor 14, as well as in other commodities such a cereals 15, forages 16, or animal products 17. However, little research has been conducted in tree nuts.…”
Section: Introductionmentioning
confidence: 99%